PENGEMBANGAN SEKOLAH RAMAH ANAK BAGI GUGUS GAJAH MADA KECAMATAN BANDAR KABUPATEN BATANG - Egar, Ngasbun; Nugrahani, Dyah; Werdiningsih, Yuli Kurniati (LPPM Universitas Widya Dharma Klaten, 2025)
The program is aimed at developing child friendly school for some schools belong to Gajah Mada Group in Batang Region. The team gives some trainings to the teachers. The materials of the training are the child friendly education concept (provision, protection, and participation); the indicators of child friendly school; and the management to develop the child friendly school. The training examines some methods, they are lecturing, discussion, accompaniment, and monitoring. After the training was done, it can be achieved that 1) all the teachers joined the lecturing on child friendly education principle; 2) a hundred precent or all the teachers take part in discussion on developing child friendly school; 3) 80% of the teachers understand the concept of child friendly education; 4) 80% of the teachers have the sufficient knowledge of child friendly school; and 5) the teachers have implemented the principles of child friendly education through the school’s program.